Karakterisasi dan Optimasi Kualitas Gula Semut Berdasarkan Variasi pH Nira Kelapa - Teltje Koapaha; Tineke M. Langi; Lucia Cecilia Mandey; Mukhlis (SINTA Journal (Science, Technology, and Agricultural), 2025)
The quality of palm sugar is greatly influenced by the characteristics of the coconut sap raw material, especially the acidity level (pH), which plays an important role in the crystallization process. The purpose of this study is to analyze the chemical characteristics (reducing sugar content, moisture content, ash content), organoleptic characteristics and panelists' preference levels (color, aroma, taste), and to determine the optimal pH of coconut sap that produces the best palm sugar quality according to quality standards. The research method used was a Completely Randomized Design (CRD) with 4 treatments of sap acidity levels (pH), namely pH 5, pH 6, pH 7, and pH 8. Each treatment was repeated 3 times. The observed parameters included moisture content, ash content, reducing sugar content, as well as an organoleptic test of panelists' preference for the color, aroma, and taste of the resulting palm sugar. The obtained data were analyzed using Analysis of Variance (ANOVA), and if there were differences among treatments, they were further tested with a 5% LSD test. The study results showed that the resulting palm sugar had: reducing sugar content (3.21-6.17%), moisture content (2.27-3.85%), ash content (7.76-21.53%), and the preference test results for color (slightly like-very like), aroma (slightly like-very like), and taste (slightly like-like). It is concluded that the sap acidity level (pH) significantly affects the moisture and ash content of palm sugar, but does not significantly affect the reducing sugar content. The best brown sugar was obtained at pH 8 treatment, which resulted in a lighter color, smooth texture, low moisture content (2.27%), ash content (15.31%), and reducing sugar content (3.21%).